Contribution of NTFPs on livelihood of forest-fringe communities in Jaldapara National Park, India. (3rd April 2019) - Lepcha, Lakpa Doma; Shukla, Gopal; Pala, Nazir Ahmad; Vineeta,; Pal, Prabhat Kumar; Chakravarty, Sumit
ABSTRACT: We expected that the indigenous communities of Jaldapara National Park depend on the non-timber forest products (NTFPs), and there would be a relationship between socioeconomic variables and their dependency on NTFPs. The study also documented the gap between prices of NTFP items at the household level and in local markets. Multistage sampling procedures were applied with a sample size of 205. The data collected were analyzed through descriptive statistics and Chi-Square (χ2) test. Insignificant values of Chi-Square (χ2) test reveal that there is no association or relationship of NTFP dependency with the socioeconomic and demographic variables of the respondents. The communities do rely on NTFPs for their daily, sociocultural, and cash requirements and assure a safety net during scarcity. There is a variable contribution of NTFPs to total monthly household income (1–70%). We documented 43 species of NTFPs sold either as raw or as processed form. The NTFPs sold were in the form of twigs, shoot, fruit, seed, leaves, mushroom, and fish. A wide gap exists between the price realized by the community from the sale of NTFPs and those sold in the local markets. This calls for institutional intervention for capacity building and empowering the community for processing or value addition and market intelligence.